(untitled) (Journal of the College of Education for Women, 2020)
The research aims at the scholars’attention to the importance and role of Arab Muslim women through books and historical studies that historians and scholars have taken up like Ibn Al-Jawzi (597 AH) and his book Safwat Al-Safwa, where he presented the conduct of worship and their words and deeds, and explained to women worshipers other aspects of their lives, such as the scientific aspect Crafts and works as well as their prominent role in preaching and religious guidance, and the impact of this on their morals and qualities. This study showed the strength of the personality of women and their high interest in worship. The importance of the study lies in knowledge.The research followed the role of Muslim women to carry the banner of Arab-Islamic civilization,culture, and preserved human thought.The Islamic community has stood up in pride and honor in front of the Muslim women who are straight and religious, as the leading scholars of preaching and guidance were asking her to preach and remind.Individuals cherished her career, as most of the women’s worshipers ’news came through their husbands, sons, or fathers, which indicates mutual respect, kindness, and love among members of the Muslim family.The researchers committed to documenting information from its sources and following the method of historical research method in investigating and supporting this with tables that count the number of female worshipers in each town.